PERANAN KEPOLISIAN DALAM PEMBINAAN PELAJAR UNTUK MENCEGAH AKSI TAWURAN DI KALANGAN PELAJAR (Studi Kasus Wilayah Hukum Polresta Padang) - Eka Periaman Zai (Jurnal Education and Development, 2019)
This study aimed to express the role of the police in establishing the students and discovering the efforts made by police ​​to overcome the brawls among the students in Padang. This research was conducted using qualitative research method by following the steps that implemented by Miles & Huberman. Data collection method that was used in this study is the observation, in-depth interviews and documentation studies. To ensure the validity of data, it was required investigated techniques by emphasizing the credibility of the data research. The informants were selected by purposive sampling and snowball sampling. The results of the research revealed that the role of the Police in establishing students to reduce the brawls among the students was done by being a builder of ceremony in many schools, holding legal counseling such as seminar, and holding other beneficial activity such as Saka Bhayangkara, Randai, Taekwondo, Silat, and Karate. Besides, the efforts of the police in the brawls anticipate that by conducting cooperation with the Department of Education in the form of a MoU. It was done because there is no specific rules about the brawls in constitution. MoU describes that the offender of brawls will be expelled from school/ returned to the parent/ guardian concerned. Based on the research, these punishments were flexible. The offenders of brawls are not always to be expelled from school but they are established first. If there is no change in students’ personality, the next punishment will be done.